2017
DOI: 10.1016/j.transproceed.2017.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Polyhydroxyethyl-Aspartamide–Polylactic Acid Scaffold for Biliary Duct Repair: A Preliminary In Vivo Evaluation

Abstract: Tissue engineering has emerged as a new approach with the potential to overcome the limitations of traditional therapies. The objective of this study was to test whether our polymeric scaffold is able to resist the corrosive action of bile and to support a cell's infiltration and neoangiogenesis with the aim of using it as a biodegradable tissue substitute for serious bile duct injuries. In particular, a resorbable electrospun polyhydroxyethylaspartamideepolylactic acid (90 mol% PHEA, 10 mol% PLA)/polycaprolac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Lee et al. and Auth et al demonstrated the formation of the efficient hepato-biliary network under coculture conditions (hepatocytes and cholangiocytes). , In addition, a number of tissue-engineered artificial bile ducts have been reported. However, integration of bile network and its incorporation in the 3D implantable constructs still remains less explored. In this regard, the whole liver decellularized matrix has gained importance because of retention of the intact biliary network .…”
Section: Challenges Faced By Implantable Technologiesmentioning
confidence: 99%
“…Lee et al. and Auth et al demonstrated the formation of the efficient hepato-biliary network under coculture conditions (hepatocytes and cholangiocytes). , In addition, a number of tissue-engineered artificial bile ducts have been reported. However, integration of bile network and its incorporation in the 3D implantable constructs still remains less explored. In this regard, the whole liver decellularized matrix has gained importance because of retention of the intact biliary network .…”
Section: Challenges Faced By Implantable Technologiesmentioning
confidence: 99%
“…These results underline the importance of a biomimetic substrate like the electrospun PCL/gel nanofibrous matrix in promoting the epithelial cell viability and functionality, as widely discussed in literature. [86][87][88][89][90] The co-culture conditions implemented in our model have allowed us to preliminarily evaluate the reciprocal influence that the HPDE-KRAS cells and the PSCs have on each other. Specifically, we observed from the confocal images the morphological changes in stellate cells that appear in a spindle shape, indicating their activation as highlighted in the study of Lee and coworkers.…”
Section: Biomaterials Science Papermentioning
confidence: 99%
“…Acellular tubular constructs were developed using multiple materials such as polylactic acid (PLA), polycaprolactone (PCL), and polyglycolic acid (PGA). 113,[115][116][117][118][119][120][121][122] Those scaffolds were designed to be completely absorbable and have proven to be replaced by a healthy, epithelized, and vascularized wall indistinguishable from the native CBD. 113,118 Despite promising results from the use of acellular tubes in animals, all studies were performed in healthy animals.…”
Section: For Biliary Diseasementioning
confidence: 99%